2022
DOI: 10.3390/nanoenergyadv2020008
|View full text |Cite
|
Sign up to set email alerts
|

Size and Semiconducting Effects on the Piezoelectric Performances of ZnO Nanowires Grown onto Gravure-Printed Seed Layers on Flexible Substrates

Abstract: Zinc oxide (ZnO) nanogenerators have attracted increasing interest in the scientific community for use in energy harvesting and mechanical sensing applications. Understanding the interplay between piezoelectricity and semiconductor physics is fundamental to enhancing these devices’ performances, although direct characterization at the nanoscale is challenging. With this work, we present a new strategy to improve piezoresponse force microscopy (PFM) measurements and analysis. This strategy was applied to study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 50 publications
5
20
0
Order By: Relevance
“…The resulting inhomogeneity is generally believed to be detrimental to the piezoelectrical properties of the sample. Conversely, a continuous coating of uniformly shaped and highly oriented structures is seen as desirable [ 71 ]. Such a uniform and oriented coating was obtained on the silicon substrates used to verify the growth conditions (see Figure 6 ).…”
Section: Methodsmentioning
confidence: 99%
“…The resulting inhomogeneity is generally believed to be detrimental to the piezoelectrical properties of the sample. Conversely, a continuous coating of uniformly shaped and highly oriented structures is seen as desirable [ 71 ]. Such a uniform and oriented coating was obtained on the silicon substrates used to verify the growth conditions (see Figure 6 ).…”
Section: Methodsmentioning
confidence: 99%
“…The resulting inhomogeneity is generally believed detrimental to piezoelectrical properties of the sample. Conversely, a continuous coating of uniformly-shaped and highly-oriented structures is seen as desirable [67]. Such a uniform and oriented coating was obtained on silicon substrates used to verify growth conditions (see Fig.…”
Section: Semmentioning
confidence: 99%
“…Thus, it is necessary to control not only the electrical conductivity and optical transmittance of the AZO thin film, but also its structural properties in order to boost the piezoelectric performance. While many research studies have shown that the AZO thin film exhibits relevant properties as a transparent electrode that can be used in many applications, there are only very few reports on its usage in piezoelectric applications, especially through its combination with ZnO NWs …”
Section: Introductionmentioning
confidence: 99%
“…While many research studies have shown that the AZO thin film exhibits relevant properties as a transparent electrode that can be used in many applications, there are only very few reports on its usage in piezoelectric applications, especially through its combination with ZnO NWs. 25 In this work, we study the possibility of using AZO thin films as an ecofriendly bottom electrode for ZnO NW-based mechanical energy transducers. These transducers can be used in energy harvesting and sensing applications.…”
Section: Introductionmentioning
confidence: 99%